2007
DOI: 10.1016/j.archoralbio.2006.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of salivary RNA by cDNA library analysis

Abstract: Oral fluid (saliva) meets the demands for a noninvasive and accessible diagnostic medium. Recent reports by our group and others described the presence and use of human RNA in saliva as a diagnostic or forensic tool, including the use for oral cancer detection. To gain insights into the integrity of salivary RNA, we examined in detail the integrity of salivary RNA by generating a cDNA library from pooled supernatant saliva of 10 healthy donors. From a library with a primary library titer of 1.3 × 10 6 cfu/mL o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 13 publications
(17 reference statements)
1
72
1
1
Order By: Relevance
“…These steps were followed with a final extension of 5 min at 72°C and cooling to 4°C. 9 All microarray raw data have been deposited in the Gene Expression Omnibus (GEO) database under series accession no. GSE7760 (http://www.ncbi.nlm.nih.…”
Section: Rt-pcr Preamplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…These steps were followed with a final extension of 5 min at 72°C and cooling to 4°C. 9 All microarray raw data have been deposited in the Gene Expression Omnibus (GEO) database under series accession no. GSE7760 (http://www.ncbi.nlm.nih.…”
Section: Rt-pcr Preamplificationmentioning
confidence: 99%
“…Saliva contains clinically discriminatory RNA and protein biomarkers of oral cancer (6 ), Sjögren syndrome (7 ), and sleep deprivation (8 ). As with archived and postmortem clinical samples, however, the low concentrations and partially fragmented and degraded nature of RNA in saliva pose challenges to microarray-based transcriptome profiling and validation via quantitative PCR (qPCR) 8 (9,10 ). The prevailing T7 in vitro transcription (IVT) amplification method (11 ) either depends solely on the existence of a poly(A) tail or uses random priming, which severely shortens transcripts and may lead to the overrepresentation of long transcripts.…”
mentioning
confidence: 99%
“…This work also demonstrated the unequivocal conclusion that the salivary RNA signals detected can neither originate from contaminating genomic DNA nor from pseudogenes, as none of the 117 sequences obtained matched the sequences of known pseudogenes or could originated from the DNA sequence of the gene [21]. Also importantly all transcripts identified by sequencing are fromhuman origin.…”
Section: Salivary Transcriptomementioning
confidence: 58%
“…Since our initial reports we have published and accumulated an abundance of additional supporting evidence, ranging from the characterization of salivary RNA [13], over assessing salivary RNA integrity by cDNA library analysis [21], to identifying and supporting the commercialization of an effective stabilizer of RNA in whole saliva, RNAprotect® Saliva (QIAGEN) [22]. Salivary cDNA library analysis showed that none of the 117 cloned mRNAs from saliva supernatant are from a pseudogene of contaminating genomic origin.…”
Section: Salivary Transcriptomementioning
confidence: 99%
“…Park et al [70] have previously shown that a transcriptome is found in saliva, and subpanels of these mRNAs can be used as oral cancer biomarkers. In 2009, Park et al [71] measured the presence of microRNAs (miRNA) in saliva and determined their potential as an additional set of oral cancer biomarkers.…”
Section: Molecular Techniques For Early Detection Of Malignant Diseasementioning
confidence: 99%